The Student Perspective: The Impact of Podcasts on EFL Students Listening Comprehension - Dinar Ayu Asyifah; Lilia Indriani (EDUVELOP, 2021)
Technological developments are very beneficial for foreign language learning, even for teachers and students themselves. One of them is the podcast media which has proven to be an easy-to-use and effective means of learning English. The research sample was taken from 30 high school students in Indonesia by using a questionnaire to explore students' perceptions about learning to listen to foreign languages ​​using podcasts. The data collection of this research uses descriptive techniques, namely describing and explaining a phenomenon or case study in schools. Most of the students taken from the questionnaire strongly agreed that podcasts are something that is effective in helping improve listening skills because they are considered to have interesting and fun features that stimulate student enthusiasm and motivate students to continue learning. However, podcasts can prove to be a tool to improve students' listening skills in EFL classes and students recommend teachers to use this media.